A CBCT based evaluation of root proximity of maxillary posterior teeth to sinus floor in a subset of Pakistani population - Momina Anis Motiwala; Aysha Arif; Robia Ghafoor (Journal of the Pakistan Medical Association, 2021)
Objectives: To evaluate the vertical relationship of the roots of maxillary posterior teeth with maxillary sinus floorand its association with age, gender and bilateral jaw symmetry. Method: The cross-sectional study was conducted at a tertiary care hospital in Karachi from June to December 2018, and comprised patients who visited the dental clinics and underwent cone-beam computed tomography scans. The scans were evaluated in the axial, coronal and sagittal planes and roots were classified using Jungs classification for proximity to maxillary sinus floor. The distance between the sinus floor and the apices of maxillary posterior teeth was measured. Data was analysed using SPSS 23. Results: There were 60 scans with 1066 roots. The most common maxillary tooth root in Type III group of Jung classification was the mesio-buccal root of the 2nd molar with the shortest mean distance of 0.44±3.05mm, followed by palatal roots of the 1st molar with the shortest mean distance of 1.58±4.01mm. The maxillary tooth root most frequent in Type I group was buccal root of 1st premolar with a mean distance of 8.15±6.65mm, and the 2nd premolar with a mean distance of 7.38±6.60mm. No significant difference was found in terms of gender and sides (p ?0.05). Conclusion: The most common root protruding in the sinus was found to be the mesio-buccal root of the 2nd molar, followed by palatal roots of the 1st molar. The most distant maxillary tooth root from the sinus was the buccal root of 1st and 2nd premolars. Continuous...